Purgatory in Historical Perspective - Isabel Moreira (St Andrews Encyclopaedia of Theology, 2023)
Purgatory is a place, state, or stage in the Christian afterlife where, after death, the soul is purged of minor, unexpiated sin so that it can be fit for heaven. ‘Purgatory’ derives from the Latin purgare (to purge) and hence as the noun purgatorium it is a place of purgation and purification. Purgatory is also (and earliest) referenced in adjectival form as in, for example, ignis purgatoriis, purging fires. In modern scholarship, a distinction can be made between capitalized ‘Purgatory’ that references official Roman Catholic doctrine, and lower-case ‘purgatory’ that references a place or space of purgation in a non-specific doctrinal or denominational context. In Catholic theology, Purgatory is a temporary abode; a soul in Purgatory is considered ‘saved’ and destined for heaven at, or sometimes before, the Last Day, the Day of Judgment. Historically, sources differed on the degree to which the soul’s pain in Purgatory was divine retribution, psychological torment, penance, and education. Traditionally, the soul’s torment in Purgatory is described as physical pain in early sources, but it is the soul that is understood to be cleansed. The duration and intensity of pain reflects the quality and degree of human sin that must be expunged before the soul can enjoy the beatific vision. Purgatory’s place and function in Christian belief and teaching is complex and has evolved over the centuries. Modern Catholic teaching on Purgatory rests on both scripture and tradition as articulated at the Second Vatican Council (Denzinger-Hünermann 2012: 4212). Thus, in addition to scriptural proof, modern believers give authority to theological and historical interpretation in asserting the existence of Purgatory and its salvific efficacy. However, the idea of postmortem purgation is ancient and is attested widely in many religious systems. Purgatory’s origins and history in Christian thought continues to be debated in modern scholarship. Sources for understanding the theology and practices associated with a belief in Purgatory include: scriptural interpretation, theological argument and speculation, visionary literature and apparitions, cultural traditions, anti-heretical affirmations, and papal and conciliar pronouncements. Belief in Purgatory involves the believer in intercessory practices aimed at establishing a continuing and beneficial relationship with the dead, and encourages a close connection between the believer and the liturgical services and pastoral guidance that the church provides. Yet even within Catholic theology there is a longstanding note of caution about claiming knowledge of the afterlife. As expressed in the ‘Letter on Certain Questions Concerning Eschatology’ published by the Sacred Congregation for the Doctrine of the Faith in 1979, confirmed by Pope John Paul II, ‘[n]either Scripture nor theology provides sufficient light for a proper picture of life after death’ (Denzinger-Hünermann 2012: 4659). For this reason, Purgatory’s existence and mode of operation is open to many interpretations. A long history of developing thought about many aspects of Christian life undergirds such a belief. Scripture and tradition (or history) guides any discussion of Purgatory as a theological belief. Historically, most of the basic elements of Purgatory were forged in the Middle Ages and so much of this article focuses on medieval theology; later approaches are largely refinements or modernizations of medieval views. This article approaches the evolution of the theology of Purgatory from three directions: an explication of Purgatory’s origins and functioning as explained in early theological writings (sections 1–5); how Purgatory achieved doctrinal status and how it influenced religious belief (section 6); and the reception of Purgatory in the modern era (sections 7–8).